A rare Down syndrome foetus with de novo 21q;21q rearrangements causing false negative results in non-invasive prenatal testing: a case report - Hui-Hui Xu; Mei-Zhen Dai; Kai Wang; Yang Zhang; Fei-Yan Pan; Wei-Wu Shi (BMC, 2020)
Abstract Background Non-invasive prenatal testing (NIPT) has been established as a routine prenatal screening to assess the risk of common foetal aneuploidy disorder (trisomy 21, 18, and 13). NIPT has high sensitivity and high specificity, but false positive and false negative results still exist. False negative NIPT results involving Down syndrome are rare, but have a high clinical impact on families and society. Case presentation We described a case of a foetus that tested "negative" for trisomy 21 (Z-score was 0.664) by NIPT based on the semiconductor sequencing platform (SSP). The foetal fraction of cell-free DNA was 16.9%; this percentage was much larger than the threshold of 4% for obtaining accurate NIPT results. However, postnatally, the newborn was diagnosed with Down syndrome with the 46,XY,der(21;21)(q10;q10),+ 21 karyotype. Conclusions We presented a case of false negative NIPT results, which may occur through biological mechanisms rather than poor quality, technical errors or negligence. It is imperative for clinical geneticists and their patients to understand that NIPT is still a screening test.